Binder Influence on Barium Hexaferrite: Comparative Analysis of PVA and Silicone Rubber in Sintered Magnets - Sipahutar, Wahyu Solafide; Putrie, Gustya Salma; Putri, Faiza Armalia; Farhan, Abi; Hafid, Muhamad (Jurnal Ilmu Fisika, 2025)
This study explores the impact of binder types—polyvinyl alcohol (PVA) and silicone rubber (SR)—on the physical, magnetic, and mechanical properties of barium hexaferrite (BaFe12O19), synthesized via mechanical alloying and sintered at 1100°C. SEM-EDX confirmed the formation of BaFe12O19 with an average particle size of around 0.7 µm. VSM results showed a saturation magnetization (Ms) of 71.17 emu/g, remanent magnetization (Mr) of 47.8 emu/g, and coercivity (Hc) of 0.33 T. The addition of PVA reduced density (3.13–3.07 g/cm³), increased porosity (17.72%–18.47%), and decreased magnetization (0.93–0.80 mT). In contrast, SR enhanced densification, leading to higher density (3.65–3.57 g/cm³), lower porosity (6.95%–7.51%), and significantly higher hardness (232.9–438.92 HV). SR also improved mechanical strength, while PVA proved more effective in reducing shrinkage and improving magnetization. These results underscore the significant role of binder type and concentration in optimizing the properties of sintered barium hexaferrite, with SR excelling in mechanical strength and PVA in magnetization.